Structuring, Recording, and Analyzing Historical Networks in the China Biographical Database - Fuller, Michael A. 1951-; Wang, Hongsu (2021)
The China Biographical Database (CBDB) is a relational database of over 450,000 individuals from pre-modern Chinese history. CBDB is distinctive as a prosopographical database in that it allows users to generate kinship and social networks for individuals—and groups of individuals—in the database. At the beginning of the project to develop CBDB, we sought models among other digital prosopography projects but realized that, with CBDB’s focus on analytic procedures and extracting data from the vast resources of the historical Chinese textual archive, we were developing a very different model for digital prosopography. This paper presents an overview of the China Biographical Database, it capacities for exploring networks, and how we are extending those capacities through the ever-broadening extraction of data from the corpora of historical sources.
Keywords: China Biographical Database project; Prosopography; Relational Database